The articulation of burgages and streets in early medieval towns - part 2. (3rd July 2017) - Haslam, Jeremy
ABSTRACT: This is the second part of an examination of one particular aspect of the planning process in new towns of the early medieval period in England which were set out on a rectilinear module. In all these planned towns, the way in which burgages were laid out at the corners of streets meeting at right angles will have always been problematical. Four towns (excluding Bridgnorth, discussed earlier), ranging in date from the late ninth to the late twelfth century, are examined to illustrate one particular way in which these spatial problems were resolved. Deductions are made from this evidence concerning the contemporaneity or otherwise of streets and burgage systems, seen as inter-functional ensembles. These observations and deductions generate new historical narratives relating to both the morphogenetic development of the towns studied and, in some cases, the wider course of the development of urbanism in general.